Republic of Armenia : First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report ;, 2005)
The staff report for the First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility on the Republic of Armenia highlights economic developments and the macroeconomic framework. Armenia's economy continues to perform strongly. Prudent fiscal and monetary policies, strong external inflows, and ongoing structural reforms have contributed to double-digit growth, low inflation, and declining poverty. Armenia's economic outlook is favorable, although not without risks. The main policy challenge is how to deal with large remittance inflows when government deposits are large and social and infrastructure needs remain pressing.